Metronomic Chemotherapy for Palliative Treatment of Malignant Oral Tumors in Dogs - Milevoj, Nina; Nemec, Ana; Tozon, Nataša (Frontiers in Veterinary Science, 2022)
The aim of this study was to evaluate the efficacy of metronomic chemotherapy in the palliative treatment of various malignant oral tumors in dogs. Our focus was to determine the effect of treatment on local disease control and to assess the tolerability and safety of the treatment in dogs with various oral malignancies. Metronomic chemotherapy with cyclophosphamide was used to treat 12 dogs and was combined with nonsteroidal anti-inflammatory drugs in 6/12 (50 %) of dogs. A clinical benefit was observed in 6/12 (50 %) patients one month and in 4/12 (33%) three months after treatment initiation. The median survival time of the dogs was 155 days (range 21-529 days). At the end of the observation period, the disease had progressed in 10/12 (83.3 %) of the patients. Sterile hemorrhagic cystitis was the most commonly reported side effect of treatment, occurring in 4/12 (33.3 %) dogs. The results of our study suggest that metronomic chemotherapy with cyclophosphamide can be, in a subset of dogs, beneficial in the palliation of malignant oral tumors.